Progressive decrease in partial pressure of end-tidal CO2 during posterior spinal fusion surgery in a child with idiopathic scoliosis and pectus excavatum: a case report - Yan Xu; Yanjun Lin; Chunling Jiang; Li Zhou (BMC Musculoskeletal Disorders)
Abstract Background Scoliosis surgery performed in a prone position may result in thoracic anatomical compression and alter local hemodynamics, increasing surgical risk, especially in patients with pectus excavatum. Most commonly, refractory hypotension is the first symptom of these circulatory changes. Here, we report a case with scoliosis and pectus excavatum under posterior spinal fusion that presented as a progressive decrease in the partial pressure of end-tidal CO2 (PETCO2) as the first symptom in the prone position. The probable reasons are analyzed, and solutions are suggested. Case presentation We presented a case of a 17-year-old child suffering from idiopathic scoliosis and pectus excavatum who underwent elective posterior spinal fusion and developed a progressive decrease in PETCO2 accompanied by refractory hypotension while in the prone position. Computed tomography chest image revealed a reduced anteroposterior diameter between the sternum and anterior vertebra. After returned to the supine position, an immediate improvement in hemodynamic status were observed. Approximately 16 min later, the patient was repositioned prone with longitudinal bolsters placed on either side of her chest. These arrangements resulted in weight load redistribution from her midanterior thorax to her upper abdomen. The patient remained prone for approximately 5 h without further complications. This method was recommended for the patient’s operation, for which there were no adverse effects. Conclusion Placing patients in a prone position poses a risk of cardiac compression, particularly for those with both scoliosis and pectus excavatum. Apart from transesophageal echocardiography, a decrease in PET CO2 should attract the attention of the surgical team to a possible cardiac compression. Longitudinal bolsters may be recommended in cases like this. Furthermore, a timely decision to return to a supine position is needed when necessary.